Costs and Limitations of Marine Synechococcus Blue-Green Chromatic Acclimation - Raisha Lovindeer; Lawrence Abbott; Hannah Medina; Katherine R. M. Mackey; Katherine R. M. Mackey (Frontiers in Marine Science, 2021)
Benefits and trade-offs of blue/green chromatic acclimation (CA4) have received limited study. We investigated the energetic costs associated with executing chromatic acclimation using a fluorescence-based calculation of light use efficiency. Using laboratory cultures and artificial light environments, we show that the delayed response to acclimation known to occur in marine Synechococcus acclimating strains (generalists) in green light do not reduce light use efficiency in green light, but that only one generalist, RCC307, with a much smaller range of acclimation, had higher light use efficiency than blue and green light specialist strains. Generalists with a wider acclimation range either had the same or >30% lower light use efficiencies in blue and green light environments. From this work, we propose that advantages from CA4 may not be geared at direct competition with other Synechococcus specialists with fixed pigment types, but may serve to expand the ecological range of Synechococcus in spectral competition with other genera. As all eight Synechococcus strains tested had higher light use efficiency in green light, regardless of a fixed or flexible light harvesting strategy, we add evidence to the suitability of the Synechococcus genus to greener ocean niches, whether stable, or variable.